Evaluation of injury to Saccharomyces rouxii YSa40 cells in low water activity/pH glycerol/CPB stress system - Yeoh, T. K.; Cheah, Yoke Kqueen; Davies, Roland (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Mid-exponential phase Saccharomyces rouxii YSa40 cells subsequently stressed at low a w/pH in the 0.64 a w/pH 3.5 glycerol/CPB system became injured. Such injury was detected by the loss of ability of the stressed population to form colonies on secondary-stress plating medium (glycerol/BM agar at 0.94 a w/pH 3.5 (lactic acid)) while colony forming ability on secondary non-stress plating medium (sugars/BM agar at 0.94 a w/pH 3.5 (lactic) was unaffected. The injury was shown to be due to sensitivity to glycerol/lactic acid. Results of the present study will be useful for achieving complete decontamination of 'Intermediate Moisture Foods' against xerotolerant molds and yeast.